Graduate Student Completion and Comprehension of Assigned Readings: A SoTL Project - Walden, Patrick; Khan, Brittany (Teaching and Learning Inquiry, 2025)
This project examined the effectiveness of two reading strategies for graduate speech-language pathology students: peer-guided questioning using social annotation and individual reading with general instructor guidance. Thirty-six students were randomly assigned to one of the strategies, alternating for four assignments. Comprehension quizzes and self-reported reading completion were assessed. Additionally, student attitudes toward assigned readings were explored pre- and post-project, along with barriers and facilitators to reading comprehension. Results showed no significant difference between the strategies in improving comprehension or the amount of reading completed. Reported barriers to reading included time constraints and complex texts, while suggested facilitators involved pre-reading preparation and vocabulary instruction. Although neither strategy proved superior, the study highlights potential instructor-led approaches to enhance student engagement and comprehension with assigned readings, such as addressing barriers and implementing facilitators. Reflection on unexamined assumptions for this project was presented.